Sistema kompleksnogo kontrolya begunov na srednye distanzii VLGIFKa - Maksimov, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Article describes the system of complex control of middle distance runners at the VLGIFK.